Load Test and Detection System of DC 600 V Locomotive Power Supply Device - 宫国顺; 王祥 (机车电传动)
According to the problems and defects of present water resistor station, necessity of locomotive power supply device load test and detection system development was declared, and the new technic scheme was proposed, which was expounded from principle, developing course, load design, control design, and protection design etc. The system has passed the field test.